Formacion de almidón retrogradado relacionado a niveles de amilosa en el almidón de papa (Solanum tuberosum) y chuñoado a niveles : Retrograded starch formation dependent on amylose level of potatoes starch (Solanum tuberosum) and chuño. - Valdivieso Molina, Fabiola; Mollinedo Portugal, Patricia (CON CIENCIA, 2021)
Introducción: La papa es el tubérculo más importante producido a nivel mundial como producto alimenticio. Una de las formas ancestrales de los países Andinos de conservación de la papa es la obtención de un producto llamado chuño, obtenido a partir de las denominadas ¨papas amargas. Existen pocos datos respecto a la composición química y nutricional del chuño y sobre los cambios producidos en el almidón durante su elaboración en el proceso de “congelado-secado” en condiciones específicas de temperatura y exposición a rayos ultravioleta. Objetivo: Realizar una revisión bibliográfica respecto a cambios producidos en la relación de amilosa y amilopectina en la composición de almidón aislado de papa y la modificación de las características de este almidón en el proceso de elaboración de chuño. Método: Metodología: La revisión bibliográfica se ha realizado con la recopilación de tres fuentes referenciales de estudios realizados sobre el chuño y su proceso de elaboración, artículos sobre la estructura del almidón de papa y otros tubérculos del mismo género, artículos de otros productos alimenticios del Altiplano boliviano y peruano, y finalmente la influencia de los cambios de la estructura del almidón en el incremento de la formación de almidón retrogradado. ABSTRACT Introduction: The potato is the most important tuber produced worldwide as a food product. One of the ancestral ways of preserving pootatoes in the Andean countries is a product called chuño (traditional Andean freeze and sun-dried potato), obtained from the so-called “bitter potatoes”. There are few data regarding the chemical and nutritional composition of chuño and the changes produced in the starch during its preparation in the “freeze-drying” process under specific conditions of temperature and exposure to ultraviolet rays. Objective: The objective of this article was to do a bibliographic review regarding changes produced in the amylose and amylopectin ratio, the composition of isolated potato starch and the modification of the characteristics of this starch in the process of making chuño. Methodology: The literature review methodology has the compilation of three reference sources of studies carried out on chuño and its production process, articles about the structure of potato starch and other tubers, research on other food products from the Bolivian and Peruvian of Altiplano and finally the influence of the changes in starch structure in relation to the increasing of retrograde starch formation. Results: The results show that the process of making chuño increases the percentage of amylose in the total starch content, which is related to the processes of exposure to UV radiation and very drastic temperature changes, ranging between -13, 5 ºC and 16 ºC. This process would lead to the activation of enzymes, such as amylases, for the catalysis of bond breaking reactions as the main route of the process; however, other causes could be evaluated. Conclusions: The higher percentage of amylose would allow the obtaining of high percentages of retrograded starch.